Analysis of flow behaviour and strain partitioning mechanism of bimetal composite under hot tensile conditions. (1st March 2020) - Li, Zhou; Zhao, Jingwei; Jia, Fanghui; Lu, Yao; Zhang, Qingfeng; Jiao, Sihai; Jiang, Zhengyi
Highlights: The unique hot flow behaviour of bimetal composite different from that of a single material was analysed. A physically-based constitutive model considering DRV and DRX softening mechanisms for bimetal composite was established. A mixture law of bimetal composite considering the strain and stress partitioning was developed. Analytical, FE and experimental investigations were conducted on the flow behaviour of bimetal composite. Abstract: The flow behaviour and strain partitioning of 2205 duplex ferritic-austenitic stainless steel/AH36 low carbon steel bimetal composite (2205/AH36 BC) were investigated at elevated temperatures in this study. A physically-based constitutive model was established to describe the flow behaviour of bimetal composite based on the stress–strain relationships obtained from hot tensile tests, which were performed on a Gleeble 3500 thermal-mechanical test simulator over the temperature range of 950–1250 °C and strain rate range of 0.01–1 s −1 . The stress and strain partitioning of bimetal composite was analysed to develop a mixture law of flow stress under those hot working conditions, due to the different strain contributions of each material on the total flow behaviour of bimetal composite. The developed constitutive model and the mixture law considering strain partitioning were both adopted to predict the stress–strain curves and used in finite element (FE) simulation model to calculate the peak loads of 2205/AH36 BC at 1000 °C. It is found that the softening mechanisms of 2205/AH36 BC changes depending on the externally imposed working temperatures and strain rates. The contribution of AH36 carbon steel layer on total stress is relatively more than that of 2205 stainless steel layer at high temperatures, as a result of the occurrence of stress partitioning. The proposed constitutive model, instead of the mixture law, is recommended to be used in the FE simulation of practical hot working of bimetal composite due to its high accuracy.